Virtual measuring instruments as means of uncertainty evaluation - Havryliv, Denys; Velgan, Roman (Видавництво Львівської політехніки, 2005)
Modern measuring instruments as highly technological, precise, multi-functional tools today are complex systems, and estimation of their uncertainty turns into a non-trivial task of science. To provide information about the probability of results, their convergence, and reproducibility, it is necessary to analyze the task-oriented measurement uncertainty. As an approach to determining the uncertainty of complex systems, to avoid the need for professionally experienced personnel and expensive “artifacts” used for evaluation, there is a method of a so-called virtual measuring instrument. In this method, the measurement process is simulated, taking into account the influence of the main disturbance parameters and conducting statistical analysis using the Monte Carlo approach. All characteristics of virtual modules repeat the properties of real devices but allow quick and qualitative evaluation of environmental parameters' effect on the accuracy, as well as the uncertainty of measurement. It allows us to evaluate the correctness of the result under the present conditions. The measurement uncertainty is usually caused by several major sources. Uncertainty depends on the method of measurement, but there are still common factors, i.e. uncertainty caused by measuring instruments, methods, operators, and environment. Among environmental influences, it is important to highlight – the change of light and temperature, which can vary widely variate at the production process, and at the same time have a crucial impact on the uncertainty of measurement. The paper presents a virtual measurement instrument method and its known implementations.
Keywords: WVirtual measuring instrument; Uncertainty evaluation; Simulation and statistical analysis of measuring uncertainty; Monte Carlo method; Coordinate-measuring machine